Tantangan Hukum Perdagangan Internasional Pasca Pandemi dalam Analisis Kebijakan Tarif dan Non-Tarif - Dimas Prasetyo; Rani Oktaviani (Universitas Sains dan Teknologi Komputer, 2025)
The post-pandemic global economy has significantly reshaped international trade dynamics, urging Indonesia to reassess its balance between national protectionism and international legal commitments. Although trade recovery has begun, Indonesia’s policy framework remains constrained by fragmented tariff and non-tariff regulations that limit transparency and predictability. This study aims to analyze the effectiveness of Indonesia’s trade policies and their alignment with the principles of the World Trade Organization (WTO). The research employs an empirical legal method with a qualitative-descriptive approach, drawing on trade data, policy documents, and interviews with eight trade officials and five business actors conducted between 2020 and 2023. The findings indicate that exports to the European Union decreased by 10.5 percent, while exports to China increased by 8.4 percent, showing a regional concentration that may weaken long-term diversification. In addition, 70 percent of practitioners confirmed that regulatory inconsistencies and administrative delays, averaging 12 percent in export processing, have reduced Indonesia’s trade competitiveness. Comparative analysis with Vietnam and Malaysia reveals that Indonesia’s digital readiness and institutional coordination are still below regional standards. The study concludes that improving regulatory coherence, institutional synergy, and digitalization is essential to enhancing legal certainty and trade efficiency. The novelty of this research lies in its empirical identification of the gap between legal protectionism and trade liberalization in Indonesia’s post-pandemic governance, providing new insights into the interaction between law, policy, and global market integration